Aspects of Metal Surface Glowing Mechanisms with Intensive Electron Beam Bombardment - I.V. Barsuk (Журнал нано- та електронної фізики)
The paper gives a brief description and analysis of the main physical processes which can have an effect on the glowing nature of metal element surfaces in different electric vacuum devices when they are bombarded by electron beams. It has been found that the electron glowing effects on metal surfaces according to the electron energy can be explained with the help of the transition scattering on plasma waves or just with the classical transition radiation effect. This fact is rather important in terms of classical physics interpretation of the observed glowing effects on metal surface elements and techniques optimization of metal and electron beams diagnostics as well.